Sonic Hedgehog potentiates BMP9-induced osteogenic differentiation of mesenchymal stem cells - Lulu Zhang; Caixia Ji; Ziyun Li; Habu Jiwa; Zhou Xie; Xiaoji Luo; Jinyong Luo (Genes and Diseases)
Bone morphogenetic protein 9 (BMP9) has remarkable potential to induce the differentiation of mesenchymal stem cells (MSCs) towards the osteoblastic lineage. Additionally, research suggests that certain growth factors have the ability to potentiate BMP9-induced osteogenic differentiation of MSCs. Sonic Hedgehog (Shh) plays an indispensable role in the regulation of skeletal development. The objective of this research was to assess the potential influence of Shh on BMP9-induced osteogenic differentiation of MSCs. Our findings indicated that Shh effectively enhanced BMP9-induced early and late osteogenic differentiation of MSCs, and increased BMP9-induced expression/transcriptional activity of osteogenesis-related transcription factors. Besides, it was observed that Shh promoted BMP9-induced ectopic bone formation of MSCs in vivo. Moreover, BMP9 was able to facilitate the repair of bone defects in rats, while Shh further accelerated this reparative process. Mechanistically, Shh enhanced the activation of the Smad1/5/8 signaling pathway which was induced by BMP9. Furthermore, GANT-61, an inhibitor of Gli1 and Gli2, attenuated the enhancing effect of Shh on BMP9-induced osteogenic differentiation of MSCs. Collectively, the co-administration of BMP9 and Shh may present a promising therapeutic approach for the treatment of fracture nonunion, delayed fracture healing, and bone defects.